Stenting of Ductus Arteriosus for Duct-Dependent Pulmonary Circulation: An Emergency and Life Saving Procedure: Stenting of Ductus Arteriosus for Duct-Dependent Pulmonary Circulation: An Emergency and Life Saving Procedure - Permitasari, Desy Ayu; Andini, Aulia Rizki; Ayukusuma, Anggita Rahma; Susilawati, Martvera; Priyatno, Agus (RSUP Dr. Kariadi, 2022)
BACKGROUND: Critical congenital heart defect with ductal-dependent pulmonary flow presents as a life-threatening condition. The patency of ductus arteriosus is required to supply blood flow into the lung. Stent implantation into ductus arteriosus has been proposed as non-surgical management for critical congenital heart disease with duct-dependent. CASE DESCRIPTION: We present full-term newborns who had critical congenital heart disease with ductal-dependent pulmonary blood blow and successfully managed with ductal stenting. Patient A, a 13-days-old male newborn had Tetralogy of Fallot-Pulmonary Atresia, restrictive Ventricular Septal Defect (VSD) and patent ductus arteriosus (PDA). Patient B, a 5-days-old female newborn had Tricuspid Atresia, restrictive VSD, PDA, and multiple congenital anomaly. Patient C, a 2-days-old female newborn had PA-IVS, PDA with stretched Patent Foramen Ovale (PFO). Prostaglandin-E1 infusion was started at first and stopped 6 hours prior to the procedure. All patients underwent ductus arteriosus stenting via femoral artery approach with drug-eluting stent. Pulmonary vascular markings were increased and oxygen saturations were improved in all of the patient. 5-month follow up, patients were in stable condition and prepared for surgical correction. DISCUSSION: Ductal stenting in patient with duct-dependent pulmonary circulation appears to be an alternative to surgery. It provides bridging palliation until the time of definitive surgery. The effectiveness of the procedure was highlighted by the fact that all the patients showed a significant improvement in arterial saturation and pulmonary vascular marking. CONCLUSION: Stenting of ductus arteriosus is feasible and safe with great result. Early detection and timely management are imperative to save the life. KEYWORDS: critical congenital heart defect, ductus arteriosus, ductal stenting, ductal-dependent pulmonary blood flow